Occurrence of a stonefish toxin-like toxin in the venom of the rabbitfish Siganus fuscescens. (15th December 2017) - Kiriake, Aya; Ishizaki, Shoichiro; Nagashima, Yuji; Shiomi, Kazuo
Abstract: Rabbitfish belonging to the order Perciformes are well-known venomous fish that are frequently involved in human accidents. However little research has been done into either the whole venom toxicities or the structures and properties of their venom toxins. In this study, we first examined biological activities of the crude venom extract prepared from dorsal spines of Siganus fuscescens, a rabbitfish most commonly found along the coasts of Japan. As a result, the crude venom extract was shown to have mouse-lethal activity, hemolytic activity against rabbit erythrocytes, edema-forming activity and nociceptive activity, similar to the known scorpaeniform fish toxins (stonefish toxins and their analogues). Then, the primary structure of the S. fuscescens toxin was successfully elucidated by the same cDNA cloning strategy as previously employed for the toxins of some scorpaeniform fish (lionfish, devil stinger and waspfish). The S. fuscescens toxin is obviously an analogue of stonefish toxins, being composed of two kinds of subunits, an α-subunit of 703 amino acid residues and a β-subunit of 699 amino acid residues. Furthermore, the genes encoding both subunits were cloned from genomic DNA and shown to have an architecture of three exons and two introns, as reported for those of the scorpaeniform fish toxins. This study is the first to demonstrate the occurrence of stonefish toxin-like toxins in perciform fish. Highlights: Biological activities of the crude toxin from rabbitfish Siganus fuscescens were similar to those of stonefish toxins. The primary structure of the S. fuscescens toxin was elucidated by cDNA cloning. The S. fuscescens toxin is an analogue of stonefish toxins, being composed of α- and β-subunits. The genes encoding both subunits of the S. fuscescens toxin contain three exons and two introns. This study is the first to clarify the occurrence of stonefish toxin-like toxins in perciform fish.